The Protection of Economic, Social and Cultural Rights in International Law - Hennie Strydom (The Constitutional Court of the Republic of Indonesia, 2019)
This contribution commences with a brief overview of the origin of economic, social and cultural rights and their eventual codification in the 1966 International Covenant on Economic, Social and Cultural Rights. The main part then focuses, firstly, on the nature and scope of state obligations for the realization of Covenant rights and the enforcement mechanisms created under the Covenant and its Optional Protocol, and secondly, on the role of the UN Human Rights Council and the UN Security Council. In the conclusion, three contemporary developments are highlighted which could open up new areas in which economic, social and cultural rights could find further application.